TO DETERMINE THE RISK FACTORS ASSOCIATED WITH ECTOPIC PREGNANCY - Basnet, Rajesh; Pradhan, Neelam; Bharati, Laxman; Bhattarai, Nirajan; Bahadur Basnet, Buddha; Sharma, Bidur (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Background Ectopic pregnancy continues to be a common life threatening condition among the women attending gynecological emergency. The study aimed to determine the risk factors associated with ectopic pregnancy. Methods A descriptive study was done in the Department of Obstetrics and Gynaecology, Â Â Tribhuvan University Teaching Hospital and Paropakar Maternity and Women's Hospital Kathmandu from May to November 2013. Women diagnosed and operated for ectopic pregnancy were interviewed using semi-structured questionnaire after second post operative day. Results Among 77 cases (44 from PMWH and 33 from TUTH) of ectopic pregnancy out of 13424 total deliveries during the study period (0.5%), the frequency of ectopic pregnancy was 1 in 79 deliveries in TUTH and 1 in 245 deliveries in PMWH. The most common presenting symptom was abdominal pain where as history of amenorrhea and vaginal bleeding was found. The peak age group was 30-34 years (n=21). Most of them were multipara 30(39%) and 61% had first pregnancy between age group of 19-24 years, 33.8% of women had home delivery with only one patient who had cesarean section in the past. 33% of the women in the study gave history of abortion and among them almost equal number of women had spontaneous abortion (n=17) or induced abortion (n=16). History suggestive of PID was found in 14 women, infertility in 10 women, ectopic pregnancy in 7 women and pelvic operation in 7 women. History of emergency contraceptive taken within 45 days of presentation was present in 18 women. Majority of patients had taken emergency contraceptive before 29-30 days. History of current use of oral contraceptive was present in 4, Depo- Provera in 7 and Cupper-T in 6 patients. Conclusion Abdominal pain was the single most common clinical presentation of ectopic pregnancy. The most identified risk factors were abortions and emergency contraceptive followed by PID, infertility, Depo provera, IUCD, and previous ectopic pregnancy. Key word: Ectopic Pregnancy, risk factor, prevalence, emergency contraceptive, temporary family planning